Time Evolution of Wigner Function in Dissipative Quantum Systems Using Entangled Trajectory Molecular Dynamics (Journal of Atomic and Molecular Sciences, 2016)
The dissipative quantum systems are treated using Klein-Kramers equation,combined with the Gaussian kernel trajectory ensemble, for time evolution of Wignerfunction $ρ_ω(q, p, t)$ in phase space. The entangled trajectory molecular dynamics approachis used to obtain trajectory solutions for the Klein-Kramers equation with threemodels: free particle, damped harmonic oscillator and metastable potential. It is foundthat the performance of semiclassical Wigner propagation is effectively for the relaxationof damped harmonic oscillator and dissipative decay of a metastable state. Inaddition, the energy of trajectory ensemble decays faster with smaller friction valueand changes slightly with variable temperature parameters.